"But It's So Random!": A Versatile Constrained Creativity Exercise for Application of Business Topics. (March 2023) - Meilich, Ofer; de Pillis, Emmeline
In this exercise, participants create a fictional business based on a set of randomly generated words. This challenge requires participants to exercise creativity, while reinforcing the business concepts learned in class. The exercise has four steps: (1) generating a prompt of three random words, (2) designing a fictional business based on this prompt, (3) answering questions applying the concepts being taught, and (4) making presentations and discussion. The exercise is followed by a debrief that includes group discussions and critical thinking activities. We illustrate the exercise with examples from a strategic management course. The exercise can be applied in a variety of topics in business and organizations, student levels, and modes of instruction. Students report that the exercise is challenging, enjoyable, and effective in increasing understanding of the concepts taught.